The Reality of Marketing of Milk in Lattakia - Ismael, Diana; Sakr, Ibrahim (Latakia University Journal -Biological Sciences Series, 2013)
This study was carried out in Lattakia province/ Syria during the 2012 season, in order to recognize the current situation of milk marketing and detect the problems and the obstacles that facing it in Lattakia. The area of study included four regions (latakia-Alhaffa- ALqurdaha and Jableh)where couple of villages in each region was studied, and the raiser were divided into categories regarding to the number of their cows. A specific questionnaires were distributed on the keepers included the following questions: farm location, holding size, the quantity of production, production costs, manufacturing costs (if present), packaging and transport costs, the marketing chain for milk, the marketing costs, the marketing margin and problems faced by the raiser. The study showed that the percentage of small farms were the largest (88.4% of the total number of farms), also showed declining numbers of raiser in recent times due to low economic efficiency of milk product, the absence of modern methods of marketing, the control of brokers who control the price, the lack of collection centers and the weakness of the role of cooperative societies and the public sector in this field.